2018
DOI: 10.1021/acs.jafc.7b05063
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Hydroxytyrosol in Experimental Diabetic Retinopathy: Relationship with Cardiovascular Biomarkers

Abstract: The aim of the study was to test the neuroprotective effect of hydroxytyrosol (HT) on experimental diabetic retinopathy. Animals were divided in four groups: (1) control nondiabetic rats, (2) streptozotocin-diabetic rats (DR), (3) DR treated with 1 mg/kg/day p.o. HT, and (4) DR treated with 5 mg/kg/day p.o. HT. Treatment with HT was started 7 days before inducing diabetes and was maintained for 2 months. In the DR group, total area occupied by extracellular matrix was increased, area occupied by retinal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…There is an increasing body of evidence about the role of antioxidants in the control of diabetic retinopathy in animal models ( Table 2 ) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing body of evidence about the role of antioxidants in the control of diabetic retinopathy in animal models ( Table 2 ) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Animal Studiesmentioning
confidence: 99%
“…In diabetic rats treated with hydroxityroxol, the total retinal thickness and the cellular size were similar to non-diabetic animals. Retinal ganglion cell loss is smaller in rats treated with hydroxytyrosol, compared with non-treated diabetic rats [ 76 ].…”
Section: Animal Studiesmentioning
confidence: 99%
“…In another study, oral administration of HT (5 mg/kg) for 7 days before and 2 months after STZ injection resulted in reductions of diabetic retinopathy symptoms [61]. HT treatment attenuated the hyperglycemia-induced decrease in number of retinal ganglion cells, and increases in retinal thickness and retinal cell size [61].…”
Section: In Vivo Evidence: Antidiabetic Effect Of Hydroxytyrosolmentioning
confidence: 99%
“…In another study, oral administration of HT (5 mg/kg) for 7 days before and 2 months after STZ injection resulted in reductions of diabetic retinopathy symptoms [61]. HT treatment attenuated the hyperglycemia-induced decrease in number of retinal ganglion cells, and increases in retinal thickness and retinal cell size [61]. Administration of HT (77 mg/kg/day) by intragastric gavage for 4 weeks decreased plasma glucose levels and markers of oxidative stress (nitric oxide (NO), malondialdehyde (MDA), while increasing levels of serum SOD and SIRT1 expression in the thoracic aorta and human umbilical vein endothelial cells (HUVEC) (Table 7) [62].…”
Section: In Vivo Evidence: Antidiabetic Effect Of Hydroxytyrosolmentioning
confidence: 99%
“…In this sense, the Alienor study, a population study based on eye diseases in the elderly, suggested a protective role for EVOO in AMD [ 22 ], and in vitro studies showed that HT might be one of the actors responsible for this beneficial effect [ 23 , 24 ]. In addition, studies in rats demonstrated the neuroprotective effect of HT in the context of diabetic retinopathy (DR) [ 25 ]. Interestingly, neuroprotective properties of EVOO in DR have also been recently associated with other components of EVOO, such as oleuropein [ 26 ].…”
Section: Introductionmentioning
confidence: 99%